Zitelle e zitellacce. Prejudices and scorn in the perception of widows and single women in Italy in the 19th century - Miscali, Monica (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
Abstract: Living alone in the pre-industrial world often created more complications for women than for men. The main source of this discrimination was a widespread prejudicial and hostile attitude towards unattached women and widows in general. Past societies have generated both pejorative and celebratory words to describe women who have never been married or were widowed. Expressions such as “old maid”, “vecchia zitella” or the slightly more benevolent expression “poor widow” have become commonplace. The aim of this paper is firstly to highlight the negative prejudices suffered by single women and widows in past centuries. Secondly, it hopes to demonstrate the considerable change in society’s attitude towards unmarried women that accompanied the rise of the bourgeois society and that transformed the semantic sense of the otherwise neutral word zitella to the pejorative one it has today. Despite focusing on the particular case of Italy, it will also seek to give a brief overview of the situation in the rest of Europe.Key words: Widows, single women, zitella, prejudices, stereotypes, ItalyRésumé: Vivre seul dans le monde préindustriel a souvent créé plus de complications pour les femmes que pour les hommes. La principale source de cette discrimination était une attitude préjudiciable et hostile envers les femmes seules et les veuves en général. Les sociétés du passé ont généré de nombreux mots péjoratifs pour décrire les femmes qui n’ont jamais été mariées ou qui étaient veuves. Combien de fois avons-nous entendu des mots tels que «old maid», ou bien «vieille fille» ou encore l’expression apparemment bienveillante “pauvre veuve”. Le but de cet article est de mettre en évidence les préjugés négatifs qui ont été employé au cours des siècles passésafin de décrire les femmes célibataires et les veuves et de montrer comment l’attitude de la société envers les femmes célibataires a considérablement changé avec la montée de la société bourgeoise qui a transformé le sens sémantique du mot “zitella” originairement neutre en un terme au sens aujourd’hui péjoratifact francese. L’article se concentrera sur les cas de l’Italie, mais il cherchera aussi à donner un bref aperçu de la situation dans le reste de l’Europe.Mots-clés: Veuves, femmes célibataires, vieille fille, préjugés, stéréotypes, zitella doi: https://doi.org/10.20318/revhisto.2017.3703